1999
DOI: 10.1111/j.1530-0277.1999.tb04049.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma‐Hydroxybutyric Acid (GHB) in the Treatment of Alcohol Withdrawal Syndrome: A Randomized Comparative Study Versus Benzodiazepine

Abstract: GHB is as effective in the management of AWS as benzodiazepine and it seems to be quicker in reducing anxiety, agitation, and depression. Both drugs are safe and well-tolerated in AWS management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 46 publications
0
40
0
4
Order By: Relevance
“…This concentration of GHB was very high compared with that hypothetically achieved in human studies (Addolorato et al, 1999). The physiological concentration of GHB in the mammalian brain ranges from 2 to 5 M, but this amount could be increased by several orders of magnitude after exogenous administration of GHB (Gobaille et al, 1999).…”
Section: ␥-Hydroxybutyric Acid and Alcohol Withdrawal 905mentioning
confidence: 84%
See 1 more Smart Citation
“…This concentration of GHB was very high compared with that hypothetically achieved in human studies (Addolorato et al, 1999). The physiological concentration of GHB in the mammalian brain ranges from 2 to 5 M, but this amount could be increased by several orders of magnitude after exogenous administration of GHB (Gobaille et al, 1999).…”
Section: ␥-Hydroxybutyric Acid and Alcohol Withdrawal 905mentioning
confidence: 84%
“…Moreover, GHB reduces self-administration of alcohol and suppresses alcohol withdrawal signs in alcohol-preferring rats (Fadda et al, 1989). A comparison between benzodiazepines and GHB in the management of alcohol withdrawal syndrome in humans revealed that GHB is as effective as diazepam and seems to reduce anxiety, agitation, and depression more rapidly (Addolorato et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Alcoholism results in an increase in morbidity and mortality, a reduced quality of life at the individual level and a variety of societal, public health and illegal consequences. Therapeutic approaches toward AUDs combine various individual and group psychotherapies, pharmacotherapy aiming at facilitating alcohol withdrawal, reducing alcohol craving and contributing to the maintenance of abstinence, psychosocial interventions and patient associations [21,22].In several randomized, placebo-or active comparator-controlled clinical studies, SO has consistently shown efficacy in the treatment of acute alcohol withdrawal syndrome [6,23,24], in the maintenance of long term alcohol abstinence [25][26][27], and in the management of treatment-resistant chronic alcoholics [28]. No serious drug-related effects have been reported for SO in clinical studies [12,29].…”
mentioning
confidence: 99%
“…dizziness, sleepiness and tiredness, usually of mild intensity, were significantly more frequent in subjects on SO than in those on placebo. These adverse effects usually occurred in the 3-4 first weeks of treatment and resolved thereafter without a need for study drug withdrawal [24,30].In the past 10 years, a growing body of literature has focused on the abuse, misuse and criminal uses of GHB [31][32][33]. Illicit GHB can lead to abuse, misuse, addiction, criminal use and/or overdosing, and may have long term neurotoxic effects [5,34].…”
mentioning
confidence: 99%
“…Besides its effectiveness in the treatment of alcohol withdrawal syndrome with effi cacy equivalent to diazepam [39] and clomethiazole [40] , GHB (50 mg/kg body weight, divided into three daily doses) decreases alcohol craving by reproducing rewarding effects and thus also reducing the number of episodes of 'relapse' [38,[41][42][43][44] . GHB is well tolerated; transient side effects, including dizziness, hyporefl exia and somnolence, have been reported [38] .…”
Section: Gamma-hydroxybutyric Acidmentioning
confidence: 99%